Exchange and Forgiveness in The Unconquered and The Kite Runner - Sharmin, Sahida (Stamford Journal of English, 2013)
DOI: http://dx.doi.org/10.3329/sje.v4i0.13495 Stamford Journal of English Vol.4 2008 pp.154-166